Willingness and Influencing Factors to Receive COVID-19 Vaccination Among Chinese Medical Students - Liu, Huan; Zhou, Zhiqing; Tao, Xiubin; Huang, Long; Zhu, Ergang; Yu, Liang; Du, Shaoling; Zhang, Ming (Frontiers in Public Health, 2022)
Objectives The aim of this study is to evaluate the desire of medical students in China to get vaccinated or not get vaccinated and the reasons for either decision. Methods A cross-sectional survey was conducted from 11 March and 12 March 2021, by administering an online questionnaire to the Chinese medical students. Data entry and analysis were conducted using IBM SPSS ver. 26.0. Results Of 3,047 students who completed the survey, 37.9% (1,154) of participants indicated that they would be vaccinated against COVID-19, while 62.1% (1,893) declared that they would not. Attitudes to the COVID-19 vaccine (p = 0.000), levels of eHealth Literacy (p = 0.000), the impact of COVID19 (p = 0.000), concerns about the COVID-19 vaccine (p = 0.000) and gender (p = 0.000) strong associations with willingness to receive the COVID-19 vaccine. Conclusion The willingness to receive COVID-19 vaccination was sub-optimal among medical students in China. Educational interventions to improve medical students' perceptions and acceptance toward the COVID-19 vaccine are needed.